THE IMPORTANCE OF THE AUDITING NURSE IN HOSPITAL INSTITUTIONS - Tiburcio, Aline Pereira Nunes (2019)
This work has as objective to verify the importance of the nurse auditor`s performance within hospital institutions. The research refers to a literature review method known systematic review. The technical skills are essential for the professional nurse auditor to develop a quality service in hospitals, focusing on the administrative improvement in the process of gains and losses and, consequently, on the improvement of the care provided to the patient. The resolution COFEN (Federal Nursing Council), 266/2001 lays out the activities related to the Nurse Auditor, establishing the duties assigned to them. Its performance will result in a restructuring overview of health production demarcated by a new management logic of organizations. It is an area that is constantly on the rise, in which professionals who have administrative profiles should seek constant updates, and a promising field that deserves attention in the job market.